Implementasi Algoritma LZY (Lempel Ziv Yabba) Dalam Mengkompresi File Illustrator Berekstensi *.Ai - Hutagalung, Dendy Frans Gunawan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
In design, the use of images and animation is very important to create a stronger message and attract the attention of the audience. Adobe Illustrator is a very popular vector graphic design program used by graphic designers, illustrators, and other creative professionals. Files with the .ai extension are typically used to store vector graphics and designs created in Adobe Illustrator. Files created with this extension have a higher resolution, so of course the file size will be much larger which requires more storage space and takes longer to send and open. This problem can be solved by compressing the data. Data compression can speed up data transmission due to smaller storage sizes in internal and external memory. There are many algorithms that can be used in data compression. One such algorithm is the LZY Algorithm. The final result of applying .ai file compression using the LZY algorithm with a compression ratio result of 90.62% and a space spacing result of 9.38%. Therefore, in this study the algorithm used is the LZY algorithm sufficient to overcome the above problems.